Making an Animal Friendly Society is Why We are All Here : The Impact of Positive and Negative Framing on Employee Subjective Well-being in Animal Rights and Animal Welfare Organisations - Jirásek, Jan (2020)
The aim of this study was to describe and understand the impact of animal rights and animal welfare organisations’ external communication on the self-reported well-being of their employees. A number of studies have documented various challenges to the well-being of activists and employees in animal- and socially-oriented organisations yet no study to date has examined how an organisation’s external communication affects the ones, who communicate – the employees themselves. This study introduced two modes of organisation’s external communication - positive and negative framing. Positive framing was defined as framing that aims to evoke positive feelings in the audience while negative framing aims to do the opposite: evoke negative feelings in them. The theoretical framework of the thesis consists of the theory of “Subjective Well-being” and of the borderline conceptual theory “Framing”. The thesis presented one research question: how positive and negative framing of animal welfare and animal rights-oriented organisations affects the well-being of their employees based on employee experience? In total, seven animal rights and animal welfare employees from three different European countries were interviewed a semi-structured manner for the study and the data was analysed using the qualitative content analysis method. Most of the interviewed employees experienced that the external communication of animal rights and welfare organisations conducted solely via positive framing had a positive impact on their well-being. One of the employees indicated that the organisations’ external communication conducted entirely via negative framing had a negative impact on the employee’s well-being. Based on employee experience, the positive impact of positive framing on employee well-being was reduced by employees’ awareness of animal rights and welfare issues. Last, perceived social support and personal relationships within the organisations were seen by the employees to positively relate to their well-being and to curb the negative impact of negative framing.